Analysis of Occupational Safety and Health at Oil Plus Filling Station Installations: Literature Review - Fanny Dimasruhin Fanny; Doni Hikmat Ramdhan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Public Fuel Filling Station Installation which is an installation for distributing fuel oil into motor vehicle fuel tanks, with a significant risk of danger. The number of work accidents that occur at fuel filling stations continues to increase from 2018-2020. Program Safety and health need to be pursued to protect workers from the possibility of accidents and work-related diseases. Objective: This research aims to determine potential dangers and prevent accidents and occupational diseases among fuel station workers. Method: This research uses the "PRISMA" literature review method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Guidances and The data source for this research comes from literature search results on the internet from databases from Science Direct and ResearchGate. Using keywords “Occupational health and safety for fuel filling installation workers” “Occupational health and safety for Hydrogen and Gas Refuelling Station” “Occupational health and safety for Electrical Vehicle” published in the last five years, from 2019 to 2024, which are indexed Q1, Q2 and Q3. Results: As many 5,657 journals were found, but 10 journals were selected that met the inclusion and exclusion criteria. Potential dangers that threaten fuel station workers include: physical factors namely physical fatigue and noise and hearing problems. Chemical factors namely toxic gasses, dangerous liquids and BTEX gas (benzene, toluene, ethylbenzene, p-xylene, o-xylene, dan m-xylene). Physiological factors, psychological fatigue and quality of work life. Safety climate as an effort to prevent accidents and work-related illnesses by implementing management safety priority and ability, management safety empowerment and management safety justice. Conclusion: Potential dangers that threaten fuel station workers are: physical factor, chemical factor and psychological factor. Safety climate by implementing safety management priorities and capabilities, management safety empowerment, and management safety justice, as well as compliance with occupational safety and health regulations such as the use of personal protective equipment to reduce the risk of danger and thus reduce the occurrence of work accidents.